MAPPING THE PARADIGM OF CONTEMPORARY MAQĀṢIDĪEXEGESIS:A Philosophical Inquiry Into The Works of Abū Zayd, Raḥmānī, and As’ad - Muhammad Maimun; Muhamad Sofi Mubarok; Mohamad Yahya (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2025)
Contemporary tafsir studies are experiencing a paradigm shift from textuality toward maqāṣid-based contextuality. However, the methodological diversity among contemporary scholars remains philosophically unmapped. This research aims to analyze the paradigmatic construction of tafsir maqāṣidī (maqāṣid-based exegesis) through the thoughts of three key figures: Waṣfī ’Ashūr Abū Zayd, Ibrahim Raḥmānī, and ‘Alī Muḥammad As’ad. Employing a qualitative library research method with a philosophy of science approach, this study examines the ontological, epistemological, and axiological aspects of their works. The findings indicate that ontologically, the three scholars concur in positioning the Qur'an as a text embodying a dynamic intentio dei (Divine intent). Epistemologically, significant differences exist; Abū Zayd emphasizes linguistic aspects and thematic induction, whereas Raḥmānī focuses on strict legal rationale ('illat) verification. Axiologically, tafsir maqāṣidī is oriented toward grounding universal Qur'anic values that offer solutions to humanitarian problems. This study concludes thattafsir maqāṣidī offers an integrative methodology that bridges the gap between the text of revelation and contemporary reality. Studi tafsir kontemporer mengalami pergeseran paradigma dari tekstualitas menuju kontekstualitas berbasis tujuan (maqāṣid). Namun, keragaman metodologi di kalangan sarjana kontemporer seringkali belum terpetakan secara filosofis. Penelitian ini bertujuan membedah konstruksi paradigmatik tafsir maqāṣidī melalui pemikiran tiga tokoh kunci: Waṣfī ’Ashūr Abū Zayd, Ibrahim Raḥmānī, dan ‘Alī Muḥammad As’ad. Menggunakan metode kualitatif-pustaka dengan pendekatan filsafat ilmu, penelitian ini menganalisis aspek ontologi, epistemologi, dan aksiologi dari karya-karya tafsir mereka. Temuan penelitian menunjukkan bahwa secara ontologis, ketiga tokoh sepakat menempatkan Al-Qur'an sebagai teks yang memuat intentio dei (maksud Tuhan) yang dinamis. Secara epistemologis, terdapat perbedaan signifikan bahwa Abū Zayd lebih menekankan aspek linguistik, sementara Raḥmānī pada illat hukum]. Secara aksiologis, tafsir maqāṣidī berorientasi pada pembumian nilai universal Al-Qur'an yang solutif bagi problem kemanusiaan. Penelitian ini menyimpulkan bahwa tafsir maqāṣidī menawarkan metodologi integratif yang menjembatani teks wahyu dan realitas kekinian.